The Nexus between Financial Leverage and Profitability: Evidence From Top-40 Johannesburg Security Exchange (JSE) Listed Companies - Matsoma, Ntomolane Lobisa (Acta Universitatis Danubius. Œconomica, 2022)
Abstract: The study investigate the nexus between financial leverage and profitability with specific reference from top-40 JSE firms. This study originate from emerging countries. It is on this background that this study attempts to investigate the connection between financial leverage and profitability from a South African viewpoint. The system generalized method of moments (GMM) was used to analyze the relationship between financial leverage and profitability. The sample of 21 of the top-40 JSE firms from 2011 to 2019 was used. The secondary data for the article were collected from Iress INET BFA database. The results of the study revealed that financial leverage has negative influence on profitability of top-40 JSE companies. Whereas other variables such as liquidity, firm size, and growth opportunity are also negatively influences profitability. The study is restricted to the top-40 JSE companies only which means cannot generalise the finding to all listed companies on JSE and different sectors of the economy. The study suggests that directors and managers should control and manage leverage as they improve the variety and the quality of the firm's profitability. This results might be beneficial for future researchers, manager and investor as a point of reference.